2003
DOI: 10.1021/bi027385d
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanism of Pseudomonas aeruginosa PhzD, an Isochorismatase from the Phenazine Biosynthetic Pathway,,

Abstract: PhzD from Pseudomonas aeruginosa is an isochorismatase involved in phenazine biosynthesis. Phenazines are antimicrobial compounds that provide Pseudomonas with a competitive advantage in certain environments and may be partly responsible for the persistence of Pseudomonas infections. In vivo, PhzD catalyzes the hydrolysis of the vinyl ether functional group of 2-amino-2-deoxyisochorismate, yielding pyruvate and trans-2,3-dihydro-3-hydroxyanthranilic acid, which is then utilized in the phenazine biosynthetic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
129
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 42 publications
1
129
0
1
Order By: Relevance
“…The crystal structure has been solved and it is a dimer in the solid state. The solution molecular mass of this enzyme was determined by a combination of light scattering and interferometric refractometry [ 16] and it is also a dimer in solution. The MALDI spectrum of this enzyme (Figure 1), using sample preparation described here, showed a major peak of homodimer at m/z 50K and a major peak at 25K of monomer with minor peaks from other high-order oligomers such as trimer and tetramer.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure has been solved and it is a dimer in the solid state. The solution molecular mass of this enzyme was determined by a combination of light scattering and interferometric refractometry [ 16] and it is also a dimer in solution. The MALDI spectrum of this enzyme (Figure 1), using sample preparation described here, showed a major peak of homodimer at m/z 50K and a major peak at 25K of monomer with minor peaks from other high-order oligomers such as trimer and tetramer.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of phzA1 accounts for the majority of phenazine production (6,49). In addition, the gene products of phzM, phzH, and phzS are required to convert the intermediate phenazine-1-carboxylic acid to other final products, including phenazine-1-carboxamide, 1-hydroxphenazine, and pyocyanin (33,34,38). Production of phenazine compounds is tightly regulated by quorum-sensing systems in P. aeruginosa.…”
mentioning
confidence: 99%
“…Isochorismatase (EC 3.3.2.1) is an enzyme (EntB) occurring in E. coli and is produced during the biosynthesis of enterobactin, an iron-chelating product derived from chorismic acid and involved in the transport of iron from the bacterial environment into the cell cytoplasm (30 -32). The phzD gene encoding an isochorismatase-related enzyme, which shares 46% identity with the EntB isochorismatase, is also known to participate in phenazine biosynthesis in Pseudomonas strains (33). Parsons et al (33) have recently reported that the structure of PhzD is remarkably similar to other structures from a subfamily of ␣/␤-hydrolase-fold enzymes, whose members are known to hydrolyze amides, phosphates, phosphonates, epoxides, and C-X bonds.…”
Section: Discussionmentioning
confidence: 99%